Reflections on the Application of Digital Design in Future Urban Construction - Wang, Qiang (Transactions on Social Science, Education and Humanities Research, 2024)
As globalization deepens, it brings new opportunities for urban construction. With the acceleration of urban planning processes and the pressures of population growth, higher demands are placed on urban construction. At the same time, rapid developments in science and technology provide new ideas and directions for urban construction. Digital design, as an emerging design concept and technical method, is becoming an important support for future urban construction. By utilizing advanced technologies such as big data, cloud computing, and artificial intelligence, digital design can achieve comprehensive optimization of urban planning, architectural design and construction, and urban management and services, bringing revolutionary changes to urban construction. Therefore, this paper explains the technological basis of digital design in current urban construction to provide a background for understanding its application. It then delves into the specific application advantages of digital design in three aspects: urban planning, architectural design and construction, and urban management and services. However, digital design still faces multiple challenges in application, such as technology, security, and privacy issues, which need to be addressed through corresponding strategies. Through in-depth research and practice, it is believed that digital design will bring more sustainable solutions to future urban construction.